Cholesterol-Lowering Phytochemicals: Targeting the Mevalonate Pathway for Anticancer Interventions - Laka, Kagiso; Makgoo, Lilian; Mbita, Zukile (Frontiers in Genetics, 2022)
There are a plethora of cancer causes and the road to fully understanding the carcinogenesis process remains a dream that keeps changing. However, a list of role players that are implicated in the carcinogens process is getting lengthier. Cholesterol is known as bad sterol that is heavily linked with cardiovascular diseases; however, it is also comprehensively associated with carcinogenesis. There is an extensive list of strategies that have been used to lower cholesterol; nevertheless, the need to find better and effective strategies remains vastly important. The role played by cholesterol in the induction of the carcinogenesis process has attracted huge interest in recent years. Phytochemicals can be dubbed as magic tramp cards that humans could exploit for lowering cancer-causing cholesterol. Additionally, the mechanisms that are regulated by phytochemicals can be targeted for anticancer drug development. One of the key tumour development and suppression role players, Tumour Protein 53 (TP53), is crucial in regulating the biogenesis of cholesterol and is targeted by several phytochemicals. This minireview covers the role of p53 in the mevalonate pathway and how bioactive phytochemicals promote p53-dependent anticancer activities.